2008
DOI: 10.1103/physrevlett.100.118301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Multivalent-Ion Mediated Attraction between DNA Molecules

Abstract: All atom molecular dynamics simulations with explicit water were done to study the interaction between two parallel double-stranded DNA molecules in the presence of the multivalent counterions putrescine (2+), spermidine (3+), spermine (4+) and cobalt hexamine (3+). The inter-DNA interaction potential is obtained with the umbrella sampling technique. The attractive force is rationalized in terms of the formation of ion bridges, i.e., multivalent ions which are simultaneously bound to the two opposing DNA molec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 23 publications
5
116
5
Order By: Relevance
“…38 Full atomic scale Molecular Dynamics simulations have revealed attractive ion bridges, i.e., multivalent ions which are simultaneously and temporarily bound to opposing DNA duplexes with a lifetime on the order of a few nanoseconds. 39 Furthermore, a small angle neutron scattering (SANS) study of the synthetic poly(styrenesulfonic acid) (PSS) has shown that the chain contracts below the Gaussian chain limit in the presence of calcium counterions. 40 The similarity in behavior of PSS and DNA suggests that the multivalent ion mediated attraction is a general phenomenon pertaining to highly charged linear polyelectrolytes.…”
Section: Effects Of Divalent Saltmentioning
confidence: 99%
“…38 Full atomic scale Molecular Dynamics simulations have revealed attractive ion bridges, i.e., multivalent ions which are simultaneously and temporarily bound to opposing DNA duplexes with a lifetime on the order of a few nanoseconds. 39 Furthermore, a small angle neutron scattering (SANS) study of the synthetic poly(styrenesulfonic acid) (PSS) has shown that the chain contracts below the Gaussian chain limit in the presence of calcium counterions. 40 The similarity in behavior of PSS and DNA suggests that the multivalent ion mediated attraction is a general phenomenon pertaining to highly charged linear polyelectrolytes.…”
Section: Effects Of Divalent Saltmentioning
confidence: 99%
“…One issue is the real nature of the commonly used condensing ions: Cobalt hexammine is a coordination metal complex; spermidine and spermine are chain-like molecules with distributed monocharges. Treating counterions as charged spheres can be flawed (20), though commonly practiced. Furthermore, the grooves of dsDNA can be binding sites for cations, and the exposed polar groups may even coordinate specific counterions (4).…”
mentioning
confidence: 99%
“…While the continuum approaches which mostly underpin the theoretical endeavors described in the paragraph above led to important insights, e.g., the significance of counterion correlations in reversing the sign of the electrostatic interactions between charged helices, backed up by detailed coarse grained simulations [41][42][43][44][45] the molecular details of the DNA solution exposed surface, the granularity of the molecular solvent, and the complicated interactions between both and the mobile charges in solution, preclude the understanding of all the relevant details. As a consequence, detailed all-atom molecular dynamics (MD) simulations appear to be the only vehicle that can bring forth a deeper understanding of the mechanisms and the relevant couplings between them [46], leading to the experimentally observed interaction and ordering phenomenology of DNA in high density mesophases [47][48][49][50][51]. On the downside, all-atom MD simulations of such complicated systems require huge computational resources and the majority of simulations aiming to describe details of the DNA solution phenomenology consist of 1-3 DNA molecules, where the focus is the counterion binding [48,52] and azimuthal dependence of DNA-DNA interaction [49].…”
Section: Simulating Dna Arraysmentioning
confidence: 99%
“…As a consequence, detailed all-atom molecular dynamics (MD) simulations appear to be the only vehicle that can bring forth a deeper understanding of the mechanisms and the relevant couplings between them [46], leading to the experimentally observed interaction and ordering phenomenology of DNA in high density mesophases [47][48][49][50][51]. On the downside, all-atom MD simulations of such complicated systems require huge computational resources and the majority of simulations aiming to describe details of the DNA solution phenomenology consist of 1-3 DNA molecules, where the focus is the counterion binding [48,52] and azimuthal dependence of DNA-DNA interaction [49]. Only recently it became feasible to set up an all-atom MD simulation for a larger set of DNA molecules [51,53] characterized by a single packing geometry with only a partial characterization of the DNA countercharge and solvent ordering.…”
Section: Simulating Dna Arraysmentioning
confidence: 99%